2008
DOI: 10.1198/016214507000001337
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of g Priors for Bayesian Variable Selection

Abstract: Zellner's g-prior remains a popular conventional prior for use in Bayesian variable selection, despite several undesirable consistency issues. In this paper, we study mixtures of g-priors as an alternative to default g-priors that resolve many of the problems with the original formulation, while maintaining the computational tractability that has made the g-prior so popular. We present theoretical properties of the mixture g-priors and provide real and simulated examples to compare the mixture formulation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
1,365
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 984 publications
(1,382 citation statements)
references
References 27 publications
9
1,365
1
7
Order By: Relevance
“…It is clearly desirable to extend the Bayes factor hypothesis test to more general scenarios such as those that involve generalized linear models (Dey, Ghosh, & Mallick, 2000) and variable selection in regression (Liang, Paulo, Molina, Clyde, & Berger, 2008). The extension of the Bayesian hypothesis test to more general statistical models is ongoing, and it is likely that MCMC-based methods will be crucial for their flexible application (e.g., Ntzoufras, 2009, chap.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…It is clearly desirable to extend the Bayes factor hypothesis test to more general scenarios such as those that involve generalized linear models (Dey, Ghosh, & Mallick, 2000) and variable selection in regression (Liang, Paulo, Molina, Clyde, & Berger, 2008). The extension of the Bayesian hypothesis test to more general statistical models is ongoing, and it is likely that MCMC-based methods will be crucial for their flexible application (e.g., Ntzoufras, 2009, chap.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…This specification is well studied and has been influential in linear modeling in statistics (e.g. Bayarri & Garcia-Donato, 2007;F. Liang, Paulo, Molina, Clyde, & Berger, 2008;Overstall & Forster, 2010).…”
Section: Additional Specificationsmentioning
confidence: 99%
“…They showed that the g-prior specification used here allowed researchers to symbolically integrate all the parameter except g! It is for this reason that the g-prior specification has been popular (see Bayarri & Garcia-Donato, 2007;F. Liang et al, 2008;Zellner, 1986).…”
Section: Model Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…These priors form an integral part of the model, and they are informed by theoretical considerations and possibly also by available prior knowledge. Selecting appropriate prior distributions is of ongoing concern to Bayesian statisticians (e.g., Kass & Wasserman, 1995;Liang, Paulo, Molina, Clyde, & Berger, 2008). In some cases, for example, if the parameter space is bounded, the absence of prior knowledge can be expressed though uniform distributions, indicating that all values within the predefined range are equally likely a priori.…”
Section: Formal Specification Of a Cognitive Toolboxmentioning
confidence: 99%